Managing of Trust and Image of Public Institutions in Poland: A Case Study of The Military and Police - Dorota KUREK (Communications of International Proceedings, 2023)
Trust in public institutions such as the military and the police, as well as the image of these entities in society, are important issues in the context of the provision by the indicated institutions of a key public good, which is public security. Increasingly, the results of surveys showing a deficit of trust in public entities are being revealed, prompting thoughts about also changing the image of public institutions in public opinion. The lack of thorough research in this area was the reason for conducting an empirical study in June 2022 in Poland on a sample of 384 Poles. The research conducted was aimed at identifying the potential dependence and/or strength of the relationship between trust in the military and police in Poland and the image of these institutions. The research and statistical analyses conducted show that the relationship between trust and the image of the military and the police is positive, which means that as the level of trust increases, the quality of the image of the two analyzed institutions also increases. In addition, a higher percentage of respondents declare trust in the military than in the police, and the image of the military is more often indicated as positive relative to indications regarding the image of the police. Respondents' opinions regarding trust and image varied by education and gender: respondents with higher education were more likely to indicate a lack of trust in the military and the police and to declare a negative image of both institutions; more men than women declared a negative image of the police.
Keywords: trust; image; public institutions; military; police